Students’ perceptions towards the drawbacks of technology in English language teaching and learning - Mohamad, Faizah; Asnawi, Muhammad Luqman; Abdul Kadir, Zaemah; Darmi, Ramiza (Macrothink Institute, 2022)
Technology has brought much improvement in English teaching and learning since its inception years ago. Undoubtedly, technology has changed the traditional English teaching and learning method, in-class, and out-of-class, with the teachers making the most of the multipurpose-functions that technology offers, especially, in this new norm era. However, as many as advantages the technology brings in English language classrooms, its drawbacks need to be addressed as well. Thus, this study aims to determine the drawbacks of technology in English language teaching and learning as perceived by university students in Malaysia.This study employed a quantitative research method using a survey design. The instrument used for this study was a set of questionnaires that was randomly distributed to students from different universities via google forms. The questionnaire consisted of 30 items which covered four sections: demographic profiles, cost of technology, language teaching using technology and language learning using technology. 85 students responded to the questionnaire and became the participants of the study. The findings revealed that university students in Malaysia perceived using technology in English language learning as the major drawback. The second drawback was the cost of technology, and finally, English language teaching using technology. The findings also revealed the students’ gender and fields of study had no influence on the drawbacks of technology in all three aspects. It can be concluded that the paradigm shift of using technology in the English language teaching and learning has also had its downside, especially in the students’ learning process.